Analysis of the Implementation of Microsoft Word to Make Student Tasks Easier Through the Instagram Stories Feature - Wulandari, Rika; Lubis, Fauzi Arif; Daulay, Aqwa Naser (Proceeding International Conference on Islamic Economics Community Services (ICIECS), 2024)
This investigates the impact of Microsoft Word on people's tasks and needs, with a focus on students. A mixed-method approach (quantitative and qualitative) was used, collecting data through Instagram story features (voting, quizzes, etc.) from 60 respondents (mostly students). The results indicate that Microsoft Word significantly helps people, especially students, with their tasks. Examples of tasks completed using Microsoft Word include essays, research papers, articles, journals, and reports